Indonesian and Australian Students' Multimodal Perceptions on Master’s English Curriculum for Global Competition: A Comparative Study - Purnomo, Maslathif Dwi; Basri, Muhammad Hasan; Manik, Nazaruddin (Register Journal, 2025)
The Master’s English curriculum in postgraduate English language education programs is essential for developing the linguistic competence, academic expertise, and professional skills required in today’s globalized era. This research compares the curricula at Indonesian Islamic Higher Education institutions and Australian universities to identify similarities, differences, and their implications for producing competitive graduates.  The study aims to align English education with global standards while integrating Islamic values. Key objectives include analyzing program structures, specializations, and content; identifying strengths and gaps; exploring innovative curricular practices; and proposing recommendations to enhance English curricula that promote both international relevance and Islamic identity. Employing a qualitative-comparative approach, this study utilized literature reviews, curriculum document analysis, stakeholder interviews, students and faculty surveys, classroom observations, and focus group discussions to gather diverse perspectives and practices. Findings reveal significant differences in pedagogical strategies, curriculum design, and philosophical orientations between the two contexts. A key area of divergence lies in how global academic standards are incorporated and balanced with Islamic educational principles. While both systems aim to prepare students for international competitiveness, Indonesian Islamic institutions focus on maintaining religious values, whereas Australian universities prioritize global benchmarks, highlighting a complex interplay between cultural identity and global educational demands. Drawing on these results, the study proposes strategic directions for curriculum development in Indonesian Islamic higher education, emphasizing the need to enhance graduates’ global competence while preserving religious and cultural integrity. The research provides valuable insights for policy formulation, curriculum innovation, and discussions on the internationalization of Islamic education.